2019
DOI: 10.1177/2325967119867676
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Injury Surveillance Study on Ski Touring

Abstract: Background: Ski touring is an outdoor sport with growing popularity in alpine countries. Information about injuries in ski touring is limited. Purpose: To determine injury rates, mechanisms, causes, and risk factors in ski touring. Study Design: Descriptive epidemiology study. Methods: Between November 2015 and May 2016, a total of 191 participants from the Alps region were prospectively tracked via personalized online questionnaires. Injury rates were calculated per 1000 hours of sports exposure. Risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
(65 reference statements)
1
15
0
2
Order By: Relevance
“…The injury rates in SB have decreased over time, however, they are still higher compared to skiers [9,10,11,12]. In slope ST, where usually a lower distance is skied compared to AS or SB [4], the data show an injury risk of 2.5 injuries per 1000 h of ST [13].…”
Section: Introductionmentioning
confidence: 99%
“…The injury rates in SB have decreased over time, however, they are still higher compared to skiers [9,10,11,12]. In slope ST, where usually a lower distance is skied compared to AS or SB [4], the data show an injury risk of 2.5 injuries per 1000 h of ST [13].…”
Section: Introductionmentioning
confidence: 99%
“…When compared with published studies in trained personnel, the knee and lower back are recognised as most frequent injury locations 17. Surveys of occupational groups working in cold weather environments have similarly identified the lower back as a common injury location 18 19. Shoulder injuries do not occur as frequently as lower limb injuries within trained military populations.…”
Section: Discussionmentioning
confidence: 98%
“…The risk of injury and mortality varies dramatically depending on the terrain (secured ski slopes, off-piste slopes, glaciers, and rock and ice slopes) where alpine ski touring is performed [42][43][44][45][46]. Studies from the Austrian Alps reported an annual death rate of 1.83 per 100,000 alpine ski tourers [47].…”
Section: (Alpine) Ski Tourersmentioning
confidence: 99%